TEACHING STRATEGIES: EFL STUDENTS’ RESPONSES TOWARD TEACHER STRATEGIES IN READING COMPREHENSION - Sri Wahyuni; Rosdiana Rosdiana; Hanifar Mardhatillah (Teunuleh Publisher, 2020)
The purpose of this study is to find out the teacher strategies in teaching reading comprehension at the first-grade students at SMA Inshafuddin Banda Aceh. This research employed a descriptive qualitative method. The participants of this research is the first grade students of SMA Inshafuddin Banda Aceh that consist of 30 students. The instruments of collecting the data used in this study is a questionnaire. The objectives of this research were to know the students’ responses of the teacher strategies in teaching reading comprehension. In this research, the result revealed that that the students’ responses toward the teacher strategies in teaching reading comprehension it showed positive responses.